Pengembangan Ensiklopedia Digital Berbasis Spasial Studi Kasus Gunung Api Semeru pada Materi Vulkanisme sebagai Penunjang Pembelajaran Geografi - Rahmawati, Dewi; Irawan, Listyo Yudha; Purwanto, Purwanto (J-PIPS (Jurnal Pendidikan Ilmu Pengetahuan Sosial), 2023)
Students see geography learning aims to instill awareness of spatial conditions in an environment, but as a rote lesson. Unlike teachers who use teaching materials that are by commercial nature. The existence of these problems, more efforts that are needed to develop digital geography teaching materials. The purpose of this research is to produce a product in the form of a digital encyclopedia.. This type of research is research and development with the ASSURE Analyze Learners model (analyzing student characteristics, learning styles, initial competencies, and curriculum analysis). State Objectives (formulating learning objectives), Select methods, media and materials (practical methods, Arcgis and Corel Draw media, volcanism and spatial materials as well as product development). Utilize Media and Materials; Require Learner Participation (product validation and trial) and Evaluate and Revise (evaluate and improve on the encyclopedia). Based on research that have been made so that it is known the value of each expert, namely 93% media experts, 85% material experts and 89% linguists, it shows that this encyclopedia has "very worthy" qualifications. When tested, students got an average score of 89% and 94% of geography teachers also had "very worthyt" qualifications. Therefore, this encyclopedia is very feasible and can be used as a support for learning geography.